Les troubles de comportement à l’adolescence et leur traitement en centre d’accueil de réadaptation à la suite d’une ordonnance de protection - Messier, Camille (Criminologie, 1990)
The author presents the main results of a study undertaken by the Youth Protection Commission. The study concerns 167 youths from 12 to 17 years of age, placed in a Quebec rehabilitation centre, in 1987-88 — under the Youth Protection Act — because of their “serious behaviour problems”. The study describes these problems and the social and judicial treatment provided to deal with them. It notes the beneficial effects of the boys' stay at the rehabilitation centre, a stay that is nonetheless difficult, according to the youngsters. Finally, the author tells of their ideas and questions, and with the results obtained, she puts forward some suggestions for improving the services to assist these young people.